Characteristics of private-sector tractor service provisions: Insights from Nigeria - Takeshima, Hiroyuki; Edeh, Hyacinth O.; Lawal, Akeem O.; Isiaka, Moshud A. (Wiley, 2015)
Agricultural mechanization has been integral to agricultural transformation during periods of development. Mechanization‐service provisions can be constrained by economies of scale, seasonality, limited mobility, or heterogeneous inputs quality. However, information has been scarce regarding how the private sector has overcome these constraints especially in countries like Nigeria that are at low agricultural development stages. We present the results of a small survey of tractor owner‐operators conducted in Nigeria. We find that existing private‐sector tractor‐hiring services in Nigeria are indeed constrained. However, we also find heterogeneity among these owner‐operators. In particular, those who buy tractors from private markets or from private individuals are more efficient than those who receive tractors through government programs, providing services to a greater area at lower costs, including during off‐peak seasons, sometimes selecting machinery types according to soil types. We conclude with a discussion of some policy implications.